"Calendar Conflicts" within the Ukrainian Greek-Catholic Community in the United States and Canada in 1950–1960 - Бабинський, А. (Київський національний університет імені Тараса Шевченка, 2020)
The article covers the "calendar conflicts" on the parishes of the Ukrainian Greek Catholic Church (Ukrainian Catholic Church) in the United States and Canada in the 1950s and 1960s, which led to the creation of parallel "old calendar" parishes in Chicago, Cleveland, Philadelphia and Washington. The arrival and adaptation of the post-war wave of Ukrainian immigrants to life in the United States and Canada were accompanied by a series of conflicts with representatives of the "old" emigration, including in the religious sphere. The desire to overcome disorientation in the new environment and to slow down the process of assimilation prompted representatives of the third wave of emigration to maximize the preservation and exacerbation of those elements of the religious tradition that would, on the one hand, more closely associated them with their homeland and, on the other, separated them from their surrounding culture. This approach did not always coincide with the desires of the descendants of previous waves of immigrants and the leadership of the UGCC in these countries, which sought a more in-depth adaptation of church life to local culture. As a result, the third wave of the Ukrainian emigration developed a phenomenon of the diasporic religion inherent for the first generations of immigrants in general, and which comprises the formation of such a religious environment (the "old" calendar became one of its elements), institutions and discourse that would connect newly arrived immigrants to their homeland and keep them from assimilation.

Висвітлено перебіг "календарних конфліктів" у громадах Української греко-католицької церкви (Української католицької церкви) в США та Канаді у 1950–1960 рр., що призвели до створення паралельних "старокалендарних" парафій у Чикаго, Клівленді, Філадельфії та Вашингтоні. Прибуття та адаптація до життя в США і Канаді повоєнної хвилі українських емігрантів супроводжувалися низкою конфліктів із представниками "старої" еміграції, зокрема й у релігійній сфері. Бажання подолати дезорієнтацію в нових умовах та прагнення пригальмувати процес асиміляції спонукали представників третьої хвилі еміграції до максимального збереження і підсилення тих елементів релігійної традиції, які б, з одного боку, міцніше пов'язували їх із батьківщиною, а з іншого – відмежовували від оточуючої культури. Такий підхід не завжди збігався із прагненнями нащадків попередніх хвиль емігрантів та проводу УГКЦ в цих країнах, що прагнули глибшої адаптації церковного життя до місцевої культури. Як наслідок, у спільнотах, що складались із представників третьої хвилі еміграції, сформувалось явище "діаспорної релігійності", притаманне першим поколінням емігрантів, що полягає у формуванні такого релігійного середовища (одним з елементів якого стал календар), інституцій і дискурсу, які б пов'язували новоприбулих емігрантів із батьківщиною і вберігали їх від асиміляції.
«Календарні конфлікти» в середовищі українських греко-католиків США і Канади у 1950–1960-х роках
Keywords: українська діаспора; діаспорна релігійність; календарні конфлікти; Йосиф Сліпий; Патріархальний рух; Josyf Slipyj; Ukrainian Patriarchate; Ukrainian Diaspora; OUN; Yaroslav Stetsko; Lev Rebet; Mykola Chubaty; Patriarchal Movement